Impact of the power generation sector on future European gas demand - Honore, A (Oxford Institute for Energy Studies, 2005)
Gas demand forecasts commonly show optimistic trends increasing gently or steeply, especially for the power sector which is seen to be the main driver for gas consumption in the next 20 years. However, high gas prices and the predominance of oil-linked prices in Continental Europe have already started to delay gas demand growth. This article surveys demand in Europe and examines possible future developments in the power generation sector.